ENHANCING CRITICAL THINKING WITH MENTIMETER PROGRAM IN HIGHER EDUCATION - Nuruddin (El Midad, 2023)
The discussion about technology, teachers, and critical thinking-oriented learning has evolved into a disposition skill with reasoning and critical pedagogical practices. Critical thinking cannot develop independently but must be fostered and engineered for students' critical reasoning connections to flourish through diverse learning media. This study aims to examine the impact of Mentimeter on critical thinking skills. The research topic is designed primarily for first-semester students. The research method is ex post facto. The data collection method employs a questionnaire that has undergone validation, reliability, normalcy, and homogeneity testing. The study's findings indicate that using Mentimeter can increase critical thinking skills, as seen by the estimated F value>F table, allowing it to be stated that the hypothesis, which claims that there